COMPARISON OF INTRA-DERMAL VERSUS CONVENTIONAL CLOSURE OF EPISIOTOMY IN TERMS OF PERINEAL PAIN (The Research of Medical Science Review, 2024)
Background: Episiotomy is a common procedure performed during vaginal delivery to prevent extensive perineal tearing. The method of episiotomy repair, including the choice of suturing technique, plays a critical role in postnatal recovery, particularly concerning perineal pain and healing.Objective: To compare the effectiveness of intra-dermal versus conventional closure techniques for episiotomy in reducing perineal pain during the first 16 hours postpartum.Methods: A randomized clinical trial was conducted in the Labour Room, Gynae and Obstetrics Unit-I, Sir Ganga Ram Hospital, Lahore, over six months after obtaining ethical approval. A total of 300 women were enrolled, with 150 women assigned to each group (Group A: Conventional Closure, Group B: Intra-dermal Closure). Participants were selected based on specific inclusion and exclusion criteria. Episiotomy was performed in all participants, and the closure technique used was either conventional or intra-dermal, depending on the group assignment. Pain was assessed using the Visual Analogue Scale (VAS) at 16 hours post-delivery.Results: The mean VAS score at 16 hours post-delivery was significantly lower in the intra-dermal closure group (4.2) compared to the conventional closure group (5.8), with a p-value < 0.001. Fewer women in the intra-dermal closure group required additional pain relief (25%) compared to those in the conventional closure group (45%) (p = 0.02). The mean time to full recovery was also shorter in the intra-dermal group (5.2 days) compared to the conventional group (7.5 days), with a p-value < 0.001.Conclusion: Intra-dermal closure of episiotomy is associated with significantly reduced perineal pain, shorter recovery times, and a lower need for additional pain relief compared to conventional closure techniques. These findings suggest that intra-dermal closure may offer a superior alternative for episiotomy repair, promoting faster maternal recovery and improving postnatal comfort.